Determinación de presencia de Tumor Venéreo Transmisible TVT en caninos de la Ciudadela La Malaria del Cantón Babahoyo Provincia de Los Ríos - Sanchez Valenzuela, Mercy Deisy (2023)
Transmissible Venereal Tumor (TVT) is classified as a pathology of great importance in suburban and urban areas of the world, due to its high ability to transmit by direct relationship, either through intercourse, sniffing or licking of the affected area to a susceptible membrane with ulcerations. These were examined and sampled by FAP cytology, swab and imprinting to determine whether they carried or not. TVT is an undifferentiated round cell tumor of histiocytic origin, characterized by bloody discharge. The present research work sought to know the presence of TVT and its association with sex, age, reproductive status, breed, and ownership in the canines of the La Malaria Citadel of the Babahoyo canton. Cytology was used as a diagnostic test, using Diff-Quick staining to observe the tumor cells of the sampled individuals. Finding that, of 100 individuals, 30% are positive for TVT, of which 23 were males and 7 females, the disease presenting in individuals over 1 year old, with genital location, predominating in dogs between 3-5 years old. Concluding that in the Citadel of La Malaria there is a presence of 30%, not influenced by age, but by sex, with males being the most predisposing and the transmission of TVT was sexual since 100% of the results showed genital injury, and at the same time they are mestizos without control over going outside, this being one of the most relevant risk elements.